PENERAPAN PEWARNAAN GRAF DALAM PEMBUATAN JADWAL MENGAJI KITAB SALAF DI PONDOK PESANTREN ASSHOLACH KEJERON - Mukhamad Azkiyak; Isnawati lujeng lestari (Center of Education Journal (CEJou), 2023)
The research aims to solve the problems that occur in Islamic boarding school Assholach Kejeron related to the arrangement of the schedule for reading the book especially at the time of the holy month of Ramadan, because students who return to school cottage to study the books of the salaf, so there is a need for a schedule arrangement study books that are structured and in accordance with the situation and conditions in the cottage pesantren, so that there is no overlap/ clash between reciting the books of the salaf. Graph coloring is a part of graph theory that can be used To solve problems regarding scheduling, there are three types: The graph coloring used is vertex, edge, Region. The type of cloud used in this study is point coloring. As for the preparation of the schedule for reading the book in this study, namely: using graph coloring with Welch Powel Algorithm. After coloring is done, it will get the chromatic number which is the minimum number of colors used in point coloring. The data that is processed into a schedule in this research are: includes: the number of teachers/supervisors who teach, the number of books to be taught teaching and the place to be used. By linking the books which will be taught as the point and the supervising teacher as the side then a graph is formed which is then colored using the algorithm welch powel, for the point coloring find the coloring result to get the number The chromatic number is then represented as a schedule recite the book in one week, with Friday and Sunday off because the day visit students in Javanese (submission of students) .